Penetrating gallbladder injury in a pediatric patient in the United States: a case report - Nelimar Cruz-Centeno; Shai Stewart; Derek R. Marlor; Charlene Dekonenko; Richard J. Hendrickson (Journal of Trauma and Injury)
Penetrating gallbladder injuries are uncommon in the pediatric population. The treatment varies according to the severity of the injury and the patient’s hemodynamics. We present the case of an 11-year-old male with an accidental pellet gunshot wound to the right upper abdomen that resulted in a grade III liver laceration and damage to the anterior gallbladder wall. The patient underwent laparoscopic cholecystectomy with drain placement. Postoperative radiography of the surgical specimen confirmed the presence of the pellet in the gallbladder. The patient recovered uneventfully and was discharged home on postoperative day 3. Laparoscopic cholecystectomy is a feasible treatment option for penetrating gallbladder injuries in hemodynamically stable patients.